Large deletion of the peroxisomal acyl-CoA oxidase gene in pseudoneonatal adrenoleukodystrophy. - Fournier, B (1994)
We have cloned the cDNA encoding human peroxisomal acyl-CoA oxidase, the first enzyme in the peroxisomal beta-oxidation of very long chain fatty acids. Its nucleotide sequence was found to be highly homologous (85%) to the rat cDNA counterpart. An 88% homology between rat and human was found in the COOH-terminal end of the cDNA which includes the Ser-Lys-Leu peroxisomal targeting signal common to many peroxisomal proteins. The gene spans approximately 30-40 kb and is poorly polymorphic. Southern blot analyses were performed in two previously reported siblings with an isolated peroxisomal acyl-CoA oxidase deficiency (pseudoneonatal adrenoleukodystrophy). A deletion of at least 17 kb, starting down-stream from exon 2 and extending beyond the 3' end of the gene, was observed in the two patients. These observations provide a molecular basis for the observed acyl-CoA oxidase deficiency in our family. In addition, our study will enable the characterization of the genetic defect in unrelated families with suspected acyl-CoA oxidase disorders.